Intraprotocol fairness and interprotocol friendliness of TFRC congestion control algorithm - L.A. Grieco; S. Mascolo (Electronics Letters, 2004)
The TCP-friendly rate control (TFRC) algorithm has been proposed for supporting applications such as video streaming or telephony over the Internet, where a relative smooth sending rate is of importance. The fairness and friendliness of TFRC over scenarios with multiple congested routers is evaluated. Results obtained using the ns-2 simulator show that while TFRC improves network utilisation with respect to Reno TCP, it exhibits a significant degree of unfairness and unfriendliness towards Reno TCP.